Functionalized nano diamond composites for photocatalytic hydrogen evolution and effective pollutant degradation. (30th October 2020) - Khan, Muhammad; Hayat, Asif; Baburao Mane, Sunil Kumar; Li, Tiehu; Shaishta, Naghma; Alei, Dang; Zhao, Ting Kai; Ullah, Azeem; Zada, Amir; Rehman, AtaUr; Khan, Wasim Ullah
Abstract: Development of superior heterogeneous photocatalyst for hydrogen (H2 ) evolution with promising pollutant degradable capacity is a significant feature but then again thought-provoking for shaping the energy and environmental issues. In this regard, a photocatalytic H2 evolution using nano diamond (ND) semiconducting materials having pollutant degradable capacity for Rhodamine B dye (RhB) has been rarely reported and hence predicted to the sustainable energy. Productive characteristics such good chemical stability, super hardness, nanometer size, biocompatibility and thermal conductivity, ND is a capable and highly valuable powder physical material. Non-uniform and agglomeration dispersion spread of ND in different solvents are the main problems preventing ND from the wide-use in commercial applications. Upon 535 nm solar light excitation, the fabricated ND sample exhibit remarkable photocatalytic H2 production with a HER of about 400 μmol h −1 than pristine ND (197 μmol h −1 ). Additionally, this H2 generation dramatically enhances the quantum yield, indicating the H2 terminated sites work as electron reservoirs. Precisely, the kinetic constant pseudo-order of FND for photodegradation of RhB was higher as compared with pristine ND. As such, the results show an important step toward tailor-designed and explain the vital role of FND composites for the rational motifs of fruitful photocatalyst with effective pollutant degradable capability for future demand. Highlights: A ball milling Functionalization of ND. An twice improved HER was observed for FND (400 μmol/h) than pure ND (197 μmol/h). Pseudo-order kinetic constant of FND for RhB was higher as compared with ND.